Survey of Comparison between Islamic Capital Venture markets with Non Islamic Capital Venture markets - Mohammadmehdi Askari; Omid Mirchooli (فصلنامه پژوهش‌های اقتصادی ایران, 2011)
Financial markets are known to face some difficulties in financing projects. While securing venture capital for high risk projects seems to be of particular importance in application of new financial tools especially those compatible with Islamic rules. Although venture capital contracts based on Islamic rules may seem more complicated than traditional contracts, but new concepts in Islamic Finance have developed and structured new financial tools and which have proven useful in financing of risky projects in developing economies in the Islamic world. This paper intends to analyze those alternative approaches  in financial market of the world